Triphosgene/Sodium Organosulfinate System: A General and Efficient Electrophilic Thiolation of Silylenol Ethers and Electron-Rich Heteroaromatics - Gao, Hai-jun; Gu, Yu-xin; Wang, Zhe-fei; Yuan, Yan-qin; Wang, Yan; Guo, Sheng-rong (Synlett, 2020)
An efficient and practical approach to electrophilic thiolation was developed by using commercially available triphosgene as a reductant and the appropriate alkyl- or arylsulfinates, which were transformed in situ into electrophilic RSCl intermediates in the presence of triphosgene. This procedure represents a general and powerful approach for the synthesis of α-(trifluoromethyl)thio-substituted ketones and thiolated electron-rich heteroaromatic compounds.
Keywords: drifluoromethylthiolation; difluoromethylthiolation; triphosgene; silylenol ethers; indoles